Планування маркетингової діяльності підприємства в сучасних умовах: інструменти і організація - Сударкіна, Світлана Петрівна; Маслій, Олексій Олександрович (НТУ "ХПІ", 2016)
Сучасна діяльність підприємств на ринку тісно пов'язана з реалізацією намічених маркетингових планів по виробництву і збуту продукції. Враховуючи економічну нестабільність в країні, виникнення ситуацій на ринку схожих з кризовими явищами, виникає актуальна проблема планування маркетингу в таких умовах. У статті розглядаються теоретичні підходи до організації маркетингу в умовах нестабільної економіки, падіння попиту і купівельної здатності. Пропонуються до використання в маркетинговому плануванні інструменти, здатні, при обмежених фінансових можливостях, створити конкурентні переваги підприємства і підвищити вірогідність реалізації намічених маркетингових планів.

The article discusses issues related to planning of marketing activity of the enterprise in modern market conditions. At the moment the market situation is characterized by the following conditions: the decline in purchasing power, decline in demand, the unstable state of the economy. An important role in this situation plays a marketing plan for the company. Not all managers correctly understand the function of marketing in business. Sometimes the enterprise in General there is no marketing service. This leads to the negative results of the action in the market. To solve this problem considers the issues of planning, formation marketing functions, choice of effective tools of marketing activities and the management and planning of marketing activities. The performed theoretical study it is proposed to use the marketing tools with low cost. Special attention should be paid to organization of marketing planning at the enterprise. Having considered separate issues on marketing planning, this paper formulates requirements for modern marketing plan. Implementation of the proposed measures should give the company the medium-term effect.
Planning of marketing activities of the enterprise in modern conditions: the instruments and the organization
Keywords: план маркетингу; інструменти маркетингу; критерії ефективності маркетингу; функції маркетингу; marketing plan; marketing tools; functions of marketing